Survei Tingkat Ketepatan Passing dan Koordinasi Mata-Kaki pada Atlet Sepakbola SSB Jatayu FC Watukelir Kabupaten Sukoharjo Tahun 2025 - Zilda Mahayudi; Kodrad Budiyono; Pipit Fitria Yulianto (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the level of eye-foot coordination and passing accuracy among 30 soccer athletes of SSB Jatayu FC Watukelir, Sukoharjo Regency, in 2025. This research employed a quantitative descriptive approach using a purposive sampling technique. Data were collected through observation of training processes and standardized tests measuring passing ability and eye-foot coordination. The collected data were analyzed using descriptive percentage techniques. The findings revealed that: (1) The athletes' passing ability was generally categorized as "good," with an average score of 12.3. The distribution consisted of 13.0% (4 athletes) in the "very good" category, 40.0% (12 athletes) in the "good" category, 30.0% (9 athletes) in the "fair" category, and 17.0% (5 athletes) in the "poor" category. (2) Eye-foot coordination among athletes was also classified as "good," with an average score of 9.86. The distribution included 17.0% (5 athletes) in the "very good" category, 37.0% (11 athletes) in the "good" category, 30.0% (9 athletes) in the "fair" category, and 17.0% (5 athletes) in the "poor" category. No athletes fell into the "very poor" category in either aspect. It can be concluded that both passing ability and eye-foot coordination of SSB Jatayu FC Watukelir athletes are generally at a good level. However, a notable proportion of athletes still fall into the fair and poor categories, indicating the need for targeted training interventions to further enhance their overall performance.